2021
DOI: 10.3390/ijms22147597
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of PPARs in Lipid Metabolism during Mycobacterial Infection

Abstract: The mycobacterial cell wall is composed of large amounts of lipids with varying moieties. Some mycobacteria species hijack host cells and promote lipid droplet accumulation to build the cellular environment essential for their intracellular survival. Thus, lipids are thought to be important for mycobacteria survival as well as for the invasion, parasitization, and proliferation within host cells. However, their physiological roles have not been fully elucidated. Recent studies have revealed that mycobacteria m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 97 publications
(120 reference statements)
0
5
0
2
Order By: Relevance
“…The liver is very crucial for lipid metabolism and lipogenesis (43), and some antiobesonenic candidates were reported to prevent obesity and serum lipid levels by regulating fat and lipid metabolism in the liver (44). The expression levels of Pnliprp, PPARs, and Cide protein family participated in the regulation of lipid digestion and metabolism, adipogenesis and adipocyte differentiation, lipid oxidation, and lipid droplet formation (45)(46)(47)(48). Our transcriptome results showed that after CGLC administration of 14 weeks, Pnliprp1, Pnliprp2, and Ppard were markedly upregulated, whereas the expression levels of Cidea and Cidec showed an obvious downregulation (Figure 7D), being consistent with the effect of Moringa oleifera leave crude polysaccharide on the expression pattern of those genes (49).…”
Section: Discussionmentioning
confidence: 99%
“…The liver is very crucial for lipid metabolism and lipogenesis (43), and some antiobesonenic candidates were reported to prevent obesity and serum lipid levels by regulating fat and lipid metabolism in the liver (44). The expression levels of Pnliprp, PPARs, and Cide protein family participated in the regulation of lipid digestion and metabolism, adipogenesis and adipocyte differentiation, lipid oxidation, and lipid droplet formation (45)(46)(47)(48). Our transcriptome results showed that after CGLC administration of 14 weeks, Pnliprp1, Pnliprp2, and Ppard were markedly upregulated, whereas the expression levels of Cidea and Cidec showed an obvious downregulation (Figure 7D), being consistent with the effect of Moringa oleifera leave crude polysaccharide on the expression pattern of those genes (49).…”
Section: Discussionmentioning
confidence: 99%
“…The mycobacterium's cell wall is rich in lipids, accounting for ≈30–40% of its total weight. [ 31 ] Upon invading host cells, mycobacteria promote the accumulation and redistribution of intracellular lipid droplets to create the necessary environment for their intracellular survival. They use host cell lipids as energy and carbon sources for intracellular proliferation while evading host immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Grabacka et al [14] summarized PPARα-specific immunomodulatory functions during infections by parasites, bacteria, and viruses, as well as the modulation of processes associated with innate immunity. Tanigawa et al [29] discussed the advancement in understanding PPARs in host-mycobacteria crosstalk via their impact on the host-dependent mechanisms of lipid metabolism, anti-inflammatory processes, and autophagy during infection. PPARγ is activated in macrophages infected with Mycobacterium leprae or Mycobacterium tuberculosis and regulates some genes involved in the uptake and accumulation of lipids and in cellular metabolism.…”
mentioning
confidence: 99%